The yeast FIT2 homologs are necessary to maintain cellular proteostasis and membrane lipid homeostasis - Yap, Wei Sheng (2022)
Lipid droplets (LDs) are implicated in conditions of lipid and protein dysregulation. The fat storage-inducing transmembrane (FIT; also known as FITM) family induces LD formation. Here, we establish a model system to study the role of the Saccharomyces cerevisiae FIT homologues (ScFIT), SCS3 and YFT2, in the proteostasis and stress response pathways. While LD biogenesis and basal endoplasmic reticulum (ER) stress-induced unfolded protein response (UPR) remain unaltered in ScFIT mutants, SCS3 was found to be essential for proper stress-induced UPR activation and for viability in the absence of the sole yeast UPR transducer IRE1 Owing to not having a functional UPR, cells with mutated SCS3 exhibited an accumulation of triacylglycerol within the ER along with aberrant LD morphology, suggesting that there is a UPR-dependent compensatory mechanism that acts to mitigate lack of SCS3 Additionally, SCS3 was necessary to maintain phospholipid homeostasis. Strikingly, global protein ubiquitylation and the turnover of both ER and cytoplasmic misfolded proteins is impaired in ScFITΔ cells, while a screen for interacting partners of Scs3 identifies components of the proteostatic machinery as putative targets. Together, our data support a model where ScFITs play an important role in lipid metabolism and proteostasis beyond their defined roles in LD biogenesis.This article has an associated First Person interview with the first author of the paper.